A Randomized Comparison of Non-Channeled GlidescopeTM Titanium Versus Channeled KingVisionTM Videolaryngoscope for Orotracheal Intubation in Obese Patients with BMI > 35 kg·m-2 - Brozek, Tomas; Bruthans, Jan; Porizka, Michal; Blaha, Jan; Ulrichova, Jitka; Michalek, Pavel (Diagnostics, 2020)
Videolaryngoscopes may improve intubating conditions in obese patients. A total of 110 patients with a body mass index > 35 kg∙m-2 were prospectively randomized to tracheal intubation using non-channeled Glidescope Titanium or channeled King Vision videolaryngoscope. The primary outcome was the time to tracheal intubation. Secondary outcomes included: total success rate, number of attempts, the quality of visualization, peri-procedural and post-proceduralcomplications. Time to the first effective breath was shorter with the King Vision (median; 95% CI)-36; 34-39 s vs. 42; 40-50 in the Glidescope group (p = 0.007). The total success rate was higher in the Glidescope group-100% vs. 89.1% (p = 0.03). There was a higher incidence of moderate and difficult laryngoscopy in the King Vision group. No difference was recorded in first attempt success rates, total number of attempts, use of additional maneuvers, intraoperative trauma, or any significant decrease in SpO2 during intubation. No serious complications were noted and the incidence of postoperative complaints was without difference. Although tracheal intubation with King Vision showed shorter time to the first breath, total success was higher in the Glidescope group, and all but one patients where intubation failed with the KingVision were subsequently intubated with the Glidescope.